Malignant priapism, review of the literature: Two cases reports (2015)
Introduction: Malignant priapism or priapism secondary to metastatic infiltration is rarely seen condition. Most patients present with extensive involvement of the primary disease, and with few options for medical or surgical management. Objectives: To describe and report two cases of malignant priapism secondary to bladder urothelial carcinoma and adenocarcinoma of prostate, respectively, as well as to perform a review of the literature. Materials and methods: Case 1. A 50 year-old patient with advanced bladder carcinoma and multifocal pulmonary metastases, who consulted due to with haematuria and priapism. Due to persistent distal necrosis priapism, he required a perineal urethrostomy and then a total penectomy. Pathology reported the involvement of penile carcinoma with thrombosis, ischaemic necrosis, and ulceration.Case 2. A 63 year-old patient with advanced prostate refractory to castration. He had a three month history of pain in penis, induration, and lower urinary tract symptoms with urinary retention managed with Foley catheter. Physical examination showed penile induration, with the penis ultrasound confirming the symptoms and the diagnosis. Conclusions: Malignant priapism is an extremely rare condition and product of a very advanced disease. Treatment options are minimal, and palliative management should be emphasised in order to improve the quality of life of patients. © 2014 Sociedad Colombiana de Urología.